2020
DOI: 10.1021/acscatal.0c02722
|View full text |Cite
|
Sign up to set email alerts
|

High Conversion to Aromatics via CO2-FT over a CO-Reduced Cu-Fe2O3 Catalyst Integrated with HZSM-5

Abstract: Direct hydrogenation of carbon dioxide (CO2) to value-added chemicals is a promising strategy to relive the greenhouse effect and replace the diminishing fossil fuels, but the huge CO2 inertness and C–C coupling barrier usually bring about numerous difficulties and count against catalytic performance. Here, a highly active and more economical composite catalyst composed of Cu-promoted Fe2O3 (nCu-Fe2O3) and HZSM-5 was developed for the selective conversion of CO2 to aromatics with 56.61% selectivity at a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 79 publications
2
66
0
Order By: Relevance
“…), using similar strategies to prepare the catalysts for CO 2 conversion is also promising. The conversion of CO 2 to C 2+ hydrocarbons could involve RWGS reaction first to produce CO, followed by syngas transformation via the FTS route. Sun et al reported that the combination of a Na-modified Fe 3 O 4 with H-ZSM-5 could produce the gasoline hydrocarbons with a selectivity of 78% at a CO 2 conversion of 22% . It was proposed that CO 2 was first converted to CO via the RWGS reaction on Fe 3 O 4 , followed by hydrogenation of CO to α-olefins (the FTS route) on χ-Fe 5 C 2 .…”
Section: Part 3: the Role Of Methanol-to-aromatics In Other Catalytic...mentioning
confidence: 99%
“…), using similar strategies to prepare the catalysts for CO 2 conversion is also promising. The conversion of CO 2 to C 2+ hydrocarbons could involve RWGS reaction first to produce CO, followed by syngas transformation via the FTS route. Sun et al reported that the combination of a Na-modified Fe 3 O 4 with H-ZSM-5 could produce the gasoline hydrocarbons with a selectivity of 78% at a CO 2 conversion of 22% . It was proposed that CO 2 was first converted to CO via the RWGS reaction on Fe 3 O 4 , followed by hydrogenation of CO to α-olefins (the FTS route) on χ-Fe 5 C 2 .…”
Section: Part 3: the Role Of Methanol-to-aromatics In Other Catalytic...mentioning
confidence: 99%
“…The stronger oxidation capability of CO 2 compared with CO makes the structural evolution more complicated in CO 2 hydrogenation. In general, Fe 3 O 4 and Fe 5 C 2 are the main phases on spent catalysts (22,23). Skrypnik et al (24) investigated the steady-state composition of Fe x O y C z catalysts (mixture of -Fe, iron carbides, and oxides) along the catalyst bed, which suggests that Fe 3 O 4 , FeO, and Fe are converted into iron carbides under reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The production of LAOs directly from CO 2 hydrogenation via the reverse water–gas-shift (RWGS) reaction followed by FTS has proven to be a promising process for CO 2 utilization; meanwhile, iron-based catalysts are a preferential alternative due to their prominent capability of catalyzing both RWGS and FTS reactions and excellent selectivity toward olefins. Due to the high activity and tunable chain growth ability of χ-Fe 5 C 2 , it is widely applied in CO 2 hydrogenation to high value-added hydrocarbons. More recently, Guo et al have even reported a LAO synthesis process directly from CO 2 hydrogenation, while selectivities of 50.3% for C 4–18 alkenes and 80% for LAOs were achieved over a biopromoted Fe catalyst (Fe/C-bio), probably due to the interaction of Fe active species and carbon.…”
Section: Introductionmentioning
confidence: 99%